2018
DOI: 10.2478/aoas-2018-0025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Zeolite Supplementation on Dairy Cow Production and Ruminal Parameters – A Review

Abstract: In recent years, the use of both natural and synthetic zeolites in livestock feeds fed to lactating cows has increased, mainly to improve their performance, health, and to protect against mycotoxins intoxication. Data of scientific literature were compiled to analyze the effects of the incorporation of non-nutritional adsorbent zeolite on production performance and ruminal environment parameters of lactating cows. At moderate levels (200–400 g/cow/day), milk yield was increased by zeolite. Milk fat and protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 62 publications
5
39
0
Order By: Relevance
“…Results of AST and albumin may be due to enhance the amino acids utilization for protein synthesis (Abdelmawla et al 1998). Data of Ca level were agree with the findings of (Marian et al 2018) when added 350g zeolite /cow/day, And Khachlouf et al (2018). On the other hand, data of blood plasma total protein, albumin and globulin values were not significantly different between treatments bentonite supplementation to the diet of growing lambs.…”
Section: Blood Serum Biochemicalsupporting
confidence: 90%
See 3 more Smart Citations
“…Results of AST and albumin may be due to enhance the amino acids utilization for protein synthesis (Abdelmawla et al 1998). Data of Ca level were agree with the findings of (Marian et al 2018) when added 350g zeolite /cow/day, And Khachlouf et al (2018). On the other hand, data of blood plasma total protein, albumin and globulin values were not significantly different between treatments bentonite supplementation to the diet of growing lambs.…”
Section: Blood Serum Biochemicalsupporting
confidence: 90%
“…Milk composition might changeable due to increase osmosis pressure in mammary follicle which increases water flow from blood into mammary follicle with fatty acids, amino acids and glucose. Khachlouf et al (2018) found that milk yield was increased by zeolite additive, while milk fat and protein contents were not altered. Also, the findings of Abd El-Baki et al (2001) demonstrated that due to the supplementation of cow diets with tafla clay with CFM plus supplemented urea treated rice straw ration, milk yield and fat percentage yield were (P˂0.05) significantly higher.…”
Section: Milk Yield and Compositionmentioning
confidence: 92%
See 2 more Smart Citations
“…In animal production, alternative products as zeolites are a solution to ensure health, productive performance (yield and quality of carcass, milk yield), to reduce the effects of mycotoxins on animal health status, to remove selectively pathogens from the animal gut without reducing microbial richness and finally to increase farm profitability. All of these effects has been extensively studied in the last decade [17][18][19][20][21][22][23][24][25][26][27][28] and are schematic represented in Figure 1.…”
Section: Introductionmentioning
confidence: 99%